2011
DOI: 10.1038/jes.2011.41
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of PM2.5 mass and components in residential and non-residential indoor microenvironments: The Sources and Composition of Particulate Exposures study

Abstract: Although short in duration, air pollutant exposures occurring in non-residential microenvironments (MEs), including restaurants, vehicles and commercial locations, can represent a large fraction of total personal exposures. For the Sources and Composition of Particulate Exposures study, a novel compact sampling system was developed, facilitating simultaneous measurement of highly speciated PM 2.5 mass in a range of commercial and residential locations. This sampler also included 1-min measurements of PM 2.5 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 27 publications
(36 reference statements)
2
35
2
Order By: Relevance
“…From the available studies that are summarized in Table 2, only two of them (Brown et al 2012;Wang et al 2006a) presented results concerning PM composition. In Atlanta, USA, Brown et al (2012) analyzed elemental compositions of PM2.5 in various microenvironments including one hospital. However, only limited results are presented for the hospital and with all data presented in plots.…”
Section: Elemental Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the available studies that are summarized in Table 2, only two of them (Brown et al 2012;Wang et al 2006a) presented results concerning PM composition. In Atlanta, USA, Brown et al (2012) analyzed elemental compositions of PM2.5 in various microenvironments including one hospital. However, only limited results are presented for the hospital and with all data presented in plots.…”
Section: Elemental Compositionmentioning
confidence: 99%
“…However, information concerning PM levels in hospitals is limited (and non-existent in Portugal). Additionally, there is a lack of knowledge on PM trace metals in these environments (Brown et al 2012;Wang et al 2006a) and the associated health impacts. Considering the importance of the hospital to public health, further studies are necessary in order to fully assess the risks of particulate exposures and related toxicity in the respective environments.…”
Section: Introductionmentioning
confidence: 99%
“…Indoor particulate matter concentrations in retail spaces was reported in 11 articles (Grimsrud et al 1999;Li et al 2001;Rea et al 2001;Sakai et al 2002;Liu et al 2004;Lee and Hsu 2007;Bennett et al 2011;Maskey et al 2011;Chan et al 2012;Brown et al 2012;Dong et al 2013). Of those studies, five studies reported PM 10 , eight studies reported PM 2.5 , one study reported PM 1 , and one study reported particle with attached polycyclic aromatic hydrocarbons (PPAH) mass concentrations.…”
Section: Measurements In Retail Storesmentioning
confidence: 99%
“…Of those studies, five studies reported PM 10 , eight studies reported PM 2.5 , one study reported PM 1 , and one study reported particle with attached polycyclic aromatic hydrocarbons (PPAH) mass concentrations. Additionally, Lee and Hsu (2007) Bennett et al (2011), andBrown et al (2012) reported ultrafine or a proxy for ultrafine (submicron, sub-3 Îźm) number concentrations. Also, one study reported chemical analysis of fine and coarse particles (Maskey et al 2011).…”
Section: Measurements In Retail Storesmentioning
confidence: 99%
See 1 more Smart Citation